WORK PERFORMANCE: THE IMPACT OF WORK ENGAGEMENT, PSYCHOLOGICAL CAPITAL, AND PERCEIVED ORGANIZATIONAL SUPPORT - Kiky Dwi Hapsari Saraswati; Mirda Sari Ningtyas Dara Pertiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Work performance, undoubtedly, is the key of organizational success. Therefore, it is very important to find out the antecedents which will significantly lead to work performance. Unlike other organizations, mental hospital is a unique institution delivering a different kind of service, both to the patients as well as the family of the patients. Adding to the fact, nurses play a very important role in determining the performance of the hospital. Current study aimed to investigate the contributions of work engagement, psychological capital, and perceived organizational support towards work performance. This was a quantitative non-experimental research employing four questionnaire distributed to 140 nurses from all positions, ranging from junior to senior, and conducted in a mental hospital in Jakarta, Indonesia. The questionnaires distributed to participants were 47-item Individual’s Work Performance, 3-item Utrecht Work Engagement Scale, 24-item Psychological Capital Questionnaire, and 8-item Survey of Perceived Organizational Support. The results of the study found that work engagement played a significant role towards work performance (F=42.402, p<0,05). Moreover, psychological capital and perceived organization support contributed a significant impact towards work engagement (F=3.678, p<0.05). Tidak diragukan lagi bahwa kinerja adalah kunci keberhasilan organisasi. Oleh karena itu, mengetahui anteseden yang secara signifikan akan mengarah pada kinerja sangat penting. Tidak seperti organisasi lain, rumah sakit jiwa adalah institusi unik yang memberikan layanan yang berbeda, baik untuk pasien maupun keluarga pasien. Ditambah juga perawat memainkan peran yang sangat penting dalam menentukan kinerja rumah sakit. Penelitian ini bertujuan untuk menyelidiki kontribusi keterlibatan kerja, modal psikologis, dan dukungan organisasi yang dirasakan terhadap kinerja kerja. Penelitian ini adalah penelitian kuantitatif non-eksperimental yang menggunakan empat kuesioner yang didistribusikan kepada 140 perawat dari berbagai posisi, mulai dari junior hingga senior, dan dilakukan di sebuah rumah sakit jiwa di Jakarta, Indonesia. Kuesioner yang dibagikan kepada peserta adalah Individual’s Work Performance yang terdiri dari 47 item, Utrecht Work Engagement Scale yang terdiri dari 3 item, Psychological Capital Questionnaire yang terdiri dari 24 item, dan Survey of Perceived Organizational Support yang terdiri dari 8 item. Hasil penelitian menemukan bahwa keterlibatan kerja berperan penting terhadap kinerja kerja (F = 42,402, p <0,05). Selain itu, modal psikologis dan dukungan organisasi yang dirasakan berkontribusi secara signifikan pada keterlibatan kerja (F = 3,678, p <0,05).